RANCANG BANGUN ALAT MESIN PENCACAH DENGAN DUA JENIS MATA PISAU MENGGUNAKAN PENGGERAK MOTOR BENSIN - Arviyanto Agung Purnomo; Yosefina Mangera; Indah Widanarti (Faculty of Agriculture, Musamus University, 2022)
The aim of the research is to produce a chopper that has two types of blades with a gasoline motor drive to chop animal feed or raw materials for making compost. This study used an experimental method by making and testing a chopper with two blades. The materials used in testing the tool were water spinach, water hyacinth, elephant grass, and banana stems. The calculations performed were a comparison of the pulley rotation speed, v-belt speed, and the effective capacity of the tool, while the test was carried out on 4 types of materials, each of which was repeated 3 times. The results showed that the counter machine with a gasoline motor drive had specifications: overall height 155 cm, front width 44 cm, width right 60 cm width left 60 cm, width of the side inlet funnel 15 cm, width of the upper intake funnel 38 cm, width of the front of the engine mount 34 cm wide side and 60 cm engine holder. The chopper's blade consists of 2 cutting blades and 16 crushing blades which can chop ingredients maximally. The distance between the blades ranges from 5-4 cm where the crushing blades are arranged alternately so that all the crushing blades can all work. The length of the cutting blade is 25 cm while the length of the crushing knife is 22 cm which is driven by a driving machine through a shaft connected by a pulley and a v-belt. The pulley rotation speed is 900 rpm, the V-belt speed is 14.5 m/s. The effective capacity of the tool for counting water spinach (109.8 kg/hour), water hyacinth (123.6 kg/hour), elephant grass (97.8 kg/hour), banana stem (171.6 kg/hour).